2008
DOI: 10.1128/jvi.02555-07
|View full text |Cite
|
Sign up to set email alerts
|

Paucity of CD4 + CCR5 + T Cells May Prevent Transmission of Simian Immunodeficiency Virus in Natural Nonhuman Primate Hosts by Breast-Feeding

Abstract: Simian immunodeficiency virus (SIV) persistence in wild populations of African nonhuman primates (NHPs) may occur through horizontal and vertical transmission. However, the mechanism(s) and timing of the latter type of transmission have not been investigated to date. Here we present the first study of SIV transmissibility by breast-feeding in an African NHP host. Six mandrill dames were infected with plasma containing 300 50% tissue culture infective doses of SIVmnd-1 on the day after delivery. All female mand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
143
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(152 citation statements)
references
References 68 publications
8
143
1
Order By: Relevance
“…Of note, these two models of persistent nonprogressive infection have pathogenic counterparts employing the same viruses, as SIVsmm can be pathogenic in rhesus macaques (RMs) (29,54) and SIVagm is pathogenic in pigtailed macaques (12,17,22; D. Mandell et al, submitted for publication). While these studies of SMs and AGMs have provided a number of important data on the pathophysiology of natural SIV infections (2,4,8,16,18,19,36,38,39,43,56), it can be argued that an approach focusing only on these two models may skew our view of a phenomenon that involves more than 40 different nonhuman primate species. Indeed, differences between SIV infections in SMs and AGMs have even been observed, and species-specific mechanisms employed for controlling disease progression have been identified (1,4,33,67).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, these two models of persistent nonprogressive infection have pathogenic counterparts employing the same viruses, as SIVsmm can be pathogenic in rhesus macaques (RMs) (29,54) and SIVagm is pathogenic in pigtailed macaques (12,17,22; D. Mandell et al, submitted for publication). While these studies of SMs and AGMs have provided a number of important data on the pathophysiology of natural SIV infections (2,4,8,16,18,19,36,38,39,43,56), it can be argued that an approach focusing only on these two models may skew our view of a phenomenon that involves more than 40 different nonhuman primate species. Indeed, differences between SIV infections in SMs and AGMs have even been observed, and species-specific mechanisms employed for controlling disease progression have been identified (1,4,33,67).…”
mentioning
confidence: 99%
“…In previous studies, we performed experimental infections of MNDs with the SIVmnd-1 (GB1) and SIVmnd-2 (MND14) reference strains and reported that both viruses show a replication pattern characterized by high peaks of viremia followed by robust levels of virus replication that are associated with transient decreases in peripheral CD4 ϩ T cell counts during the chronic phase of infection (30,31,43,60). Of note, this initial assessment involved only the major T cell populations (i.e., CD4 ϩ and CD8 ϩ T cells) and included a relatively short follow-up period (30,31,43).…”
mentioning
confidence: 99%
“…This could result from the generation and homing of vaccine-elicited CD4+ T cells to the portal of entry, which in turn mitigates the beneficial effects of the vaccine-elicited humoral immune response (38-40). Indeed, the efficiency of horizontal and vertical SIV transmission in NHP hosts in the absence of vaccination is linked to the availability of susceptible target cells in the mucosa (41)(42)(43). Furthermore, there is strong evidence that genital inflammation reduces the stringency of HIV-1 transmission (25,44,45) and increased target cell availability increases the risk of HIV-1 superinfection (46).…”
Section: Discussionmentioning
confidence: 99%
“…Mandrills 2I and 5A4 and rhesus macaques 93057, 93183A and P9110A were inoculated with 500 ml plasma containing 7.5610 6 RNA copies of SIVmnd-1 (strains 16C and 12A3) (Pandrea et al, 2008a). Mandrills 12D4 and 2H and rhesus macaques 93036, 93183B and 93046A were inoculated with 400 ml plasma containing 2.8610 7 RNA copies of SIVmnd-2 (strain 10I) .…”
Section: Methodsmentioning
confidence: 99%